Short Note: Mineral Composition of Eocene and Miocene Sandstones in Java Island - Herman Darman; Budi Muljana; J. T. van Gorsel (Ikatan Ahli Geologi Indonesia, 2013)
A number of studies discuss the mineral compositions of Cenozoic sandstones in Java Island, Some sandstones are dominated by quartz, derived from granitic and/or metamorphic basement terrains or reworked sediments; many others are dominated by lithics and plagioclase feldspars derived from andesitic volcanics. The distribution of these two end-members varies through space and time, and has not been systematically been document for all of Java.The purpose of this short note is to contribute to the subject of Java sandstone provenance by summarizing quantitative analyses on sandstone compositions in the recent studies by Muljana and Watanabe (2012), Darman (1991), Siemers et al (1992) and Smyth et al (2008) and provide some additional data points as QFL (Quartz- Feldspar- Lithics) ternary plots.